Open Innovation in Micro, Small and Medium-Sized Enterprises - Leitão, João; Dana, Léo-Paul (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book unveils the importance of micro, small, medium, and large firms for fostering open innovation, using methodological designs based on both qualitative and quantitative approaches. Several dimensions of the inbound and outbound open innovation strategies and practices are explored, in the scope of University-University, University-Industry, and University-Society relations.